Extracellular ST6GAL1 regulates monocyte–macrophage development and survival. (2nd June 2022) - Rusiniak, Michael E; Punch, Patrick R; Hait, Nitai C; Maiti, Aparna; Burns, Robert T; Chapla, Digantkumar; Moremen, Kelley W; Zhao, Peng; Wells, Lance; Hoffmeister, Karin; Lau, Joseph T Y
Abstract: Interaction of immune cells with the systemic environment is necessary for the coordinated development and execution of immune responses. Monocyte-macrophage lineage cells reside at the junction of innate and adaptive immunity. Previously we reported that the sialyltransferase ST6GAL1 in the extracellular milieu modulates B cell development and IgG production, granulocyte production, and attenuates acute airway inflammation to bacterial challenge in mouse models. Here, we report that extracellular ST6GAL1 also elicits profound responses in monocyte-macrophage lineage cells. We show that recombinant ST6GAL1 adheres to subsets of thioglycolate-elicited inflammatory cells in the mouse peritoneum and to cultured human monocyte THP-1 cells. Exposure of the inflammatory cells to recombinant ST6GAL1 elicited wholesale changes in the gene expression profile of primary mouse myeloid cells; most notable was the striking up-regulation of monocyte-macrophage and monocyte-derived dendritic cell development pathway signature genes and transcription factors PU.1, NFκB and their target genes, driving increased monocyte-macrophage population and survival ex vivo. In the cultured human monocyte cells, the essential cell surface receptor of the monocyte-macrophage lineage, the M-CSF receptor (M-CSF-R, Csfr1) was a target of extracellular ST6GAL1 catalytic activity. Extracellular ST6GAL1 activated the M-CSF-R and initiated intracellular signaling events, namely, the nuclear translocation of NFκB subunit p65, and phosphorylation of ERK 1/2 and AKT. The findings implicate extracellular ST6GAL1 in monocyte development by a mechanism initiated at the cell surface and support an emerging paradigm of an extracellular glycan-modifying enzyme as a central regulator coordinating immune hematopoietic cell development and function.